Citizen Trust Towards Border Governing Agencies at Border Crossing Points of Nepal (Patan Prospective Journal, 2023)
This article based on citizen trusts is the most important lifeline of good governance. Border governance can be achieved only by acquiring citizen trust and confident. The objective of this papers to examine the citizen trust towards border governing agencies at the border crossing points and to analyze various determinant factors of citizens’ trust. The research follows by the sequential explanatory research design using both primary and secondary sources. Primary data are extracted from stratified sampling technique using five points, Likert- scales questionnaire where 1850 responses were acquired from 10 border crossing points of Nepal. The findings shows that border governing has a citizen trust of 65.44 percent and all the determinant factors of citizen trust are correlated. The regression analysis shows that determinant factor of border governing agencies have 85 percent effect in citizen trust. The study suggest on enhancing all the determinant factors of citizen trust of all border governing agencies by incorporating required law necessary to improve border governance of Nepal.